Analysis of polymerization time on abrasive wear of dental resins - Bianchi, Eduardo Carlos [UNESP]; De Martins Ulhôa, Michele Paoline [UNESP]; Aguiar, Paulo Roberto [UNESP]; De Freitas, César Antunes; De Magalhaes Bento Goncalves, Gilberto [UNESP] (Universidade Federal de São Carlos (UFSCar), Dept Engenharia Materials, 2010)
An evaluation was made of the abrasive wear of six composite thermofxed dental resins subjected to different polymerization times. The method of evaluation was based on sharpness measurements to quantify the abrasive wear resistance of the resins. To this end, a test bench was built, consisting of a rotating porcelain cylinder that wears out a resin-coated cylinder placed above it, thus causing vertical displacement of the contact as the wear progresses. The values of vertical displacement, i.e., the input variables, were read and recorded by means of a computer program to obtain the sharpness values. These data indicated that the resins displayed different behaviors as a function of the polymerization times applied, reinforcing the importance of using a practical and rapid method of analysis in order to ensure that the behavior of new materials is fully understood before they are launched on the market.
Keywords: Abrasive wear; Composite resins; Photopolymerization time; Sharpness; Abrasive wear resistance; Abrasive wears; Coated cylinder; Computer program; Dental resins; Input variables; New material; Polymerization time; Rapid method; Test benches; Vertical displacements; Abrasion; Abrasives; Cylinders (shapes); Dental materials; Photopolymerization; Resins; Wear resistance